PENGARUH KOMISARIS INDEPENDEN, DEBT TO EQUITY RATIO DAN RETURN ON ASSET TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Perusahaan Sub Sektor Pariwisata, Restoran Dan Hotel Yang Terdaftar Di Bursa Efek Indonesia) - Salza Adzri Arismutia; Meysi (Akademi Pariwisata NHI Bandung, 2022)
The purpose of this study was to detemine the effect of Commissary Independent, Debt to Equity Ratio and Return on Asset on Audit Delay with Firm Size as a Moderating Variable. Data was taken with non-probability sampling with purposive sampling. Data analysis used Moderating Regression Analysis. Data prosessing using IBM SPSS 25.0 programme. Based on the result of the study, it can be concluded that: (1) Commissary Independent (Xâ‚) has no effect and is not signifficant on Audit Delay (Y). (2) Debt to Equity Ratio (Xâ‚‚) has no effect and is not signifficant on Audit Delay (Y). (3) Return on Asset (Xâ‚ƒ) has a negative and siginifficant effect on Audit Delay (Y). (4) Commissary Independent (Xâ‚), Debt to Equity Ratio (Xâ‚‚), and Return on Asset (Xâ‚ƒ) have a simultaneous effect on Audit Delay (Y). (5) Firm Size (Z) cannot moderate and no signifficant effect of the Commissary Independent (Xâ‚) on Audit Delay (Y). (6) Firm Size (Z) cannot moderate and no signifficant effect of the Debt to Equity Ratio (Xâ‚‚) on Audit Delay (Y). (7) Firm Size (Z) cannot moderate and no signifficant effect of the Return on Asset (Xâ‚ƒ) on Audit Delay (Y). (8) Commissary Independent (Xâ‚), Debt to Equity Ratio (Xâ‚‚), and Return on Asset (Xâ‚ƒ) with Firm Size (Z) as Moderating Variable have a simultaneous effect on Audit Delay (Y) Keywords : Commissary Independent, Debt to Equity Ratio, Retun On Asset, Audit Delay, Firm Size